2020
DOI: 10.1002/mbo3.1039
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of dibenzopyrenes on bacterial community isolated from Gulf of Mexico sediment

Abstract: The presence of polycyclic aromatic hydrocarbons (PAHs) in marine environments as a result of contamination is an environmental concern, especially in regions where oil spills such as the Deepwater Horizon have occurred. While numerous PAHs have been studied for their effects on microbes, the family of dibenzopyrenes has yet to be investigated. In this preliminary study, the impacts of these molecules on the community structure of a bacterial consortium isolated from oil‐impacted Gulf of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Members of the genus Mycobacterium are also known degraders of various aromatic hydrocarbons, which was confirmed by discovery of the relevant genes [ 12 ]. Despite the fact that bacteria of the genus Blastopirellula are found in oil-contaminated habitats, we have not found evidence that these microorganisms are involved in the degradation of hydrocarbons [ 63 ]. Uncultivated representatives of the Rhodobacteraceae family were identified in most of the samples studied.…”
Section: Resultsmentioning
confidence: 99%
“…Members of the genus Mycobacterium are also known degraders of various aromatic hydrocarbons, which was confirmed by discovery of the relevant genes [ 12 ]. Despite the fact that bacteria of the genus Blastopirellula are found in oil-contaminated habitats, we have not found evidence that these microorganisms are involved in the degradation of hydrocarbons [ 63 ]. Uncultivated representatives of the Rhodobacteraceae family were identified in most of the samples studied.…”
Section: Resultsmentioning
confidence: 99%
“…Gammaproteobacteria is one of the widely documented key classes related to oil degradation, with essential members such as the Oceanospirilales order and their genus Alcanivorax which use hydrocarbons as their primary source of carbon. [44][45][46][47] These microorganisms are known to be detected at the earlier stages during oil spills, giving way to different species with time, 44,46,47 which could explain their decrease in numbers during long periods, such as the 112 days of oil contamination. Another essential factor rests in the anaerobic environment present in the sediment, as this impacts the metabolism of these individuals.…”
Section: Desulfobacteria Shows Enhanced Colonization Of Marine Sedime...mentioning
confidence: 99%
“…[79][80][81][82] Nevertheless, it has also been shown that, even at low abundance, some key microorganisms are still important during oil spill bioremediation and the overall health of the local microbial community. 44,47 Therefore, that can also be the case where even if they are at low abundances, their role is still the same when acting alongside other hydrocarbon-degrading microorganisms.…”
Section: Modularity Shows Specialized Biodegradation Activitymentioning
confidence: 99%